2015
DOI: 10.1186/s12891-015-0684-1
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C as a potential predictor of osteoprotegerin levels in healthy men, a cross-sectional, observational study

Abstract: BackgroundThe aim of the present study is to evaluate serum osteoprotegerin (OPG) and soluble receptor activator of nuclear factor κB ligand (sRANKL) levels in a randomly selected male cohort over 50 years of age and its association with cystatin C, a cysteine proteinase inhibitor that decreases formation of osteoclasts by interfering at a late stage of pre-osteoclast differentiation, apart from being a marker of renal function independent of gender, muscle mass and age; in addition to known predictors such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…In this context, we also found a significant positive correlation with cystatin‐C. In a recent observational study, Kulcsar‐Jakab et al demonstrated that cystatin‐C is a potential predictor of OPG levels in healthy men. Moreover, It has been shown that cystatin‐C could be used as a marker for cardiovascular risk assessment .…”
Section: Discussionsupporting
confidence: 80%
“…In this context, we also found a significant positive correlation with cystatin‐C. In a recent observational study, Kulcsar‐Jakab et al demonstrated that cystatin‐C is a potential predictor of OPG levels in healthy men. Moreover, It has been shown that cystatin‐C could be used as a marker for cardiovascular risk assessment .…”
Section: Discussionsupporting
confidence: 80%
“…The role of CST5 was previously revealed in colorectal cancer, in which loss of CST5 promoted tumour differentiation while induction of CST5 exerted a tumour‐suppressive effect on colorectal cancer . More importantly, as a cysteine proteinase inhibitor, CST5 could restrain osteoclast formation through interference of late‐staged differentiation of pre‐osteoclasts . TRAP was known to be an osteoclast marker, and the increased expression of TRAP was exhibited in osteoblasts and osteocytes in experimental OP rats .…”
Section: Discussionmentioning
confidence: 90%
“…CST5, a cysteine protease inhibitor, has been reported to be associated with tumour suppression, but there was little research focusing on the effect of CST5 on OP. The role of another cysteine protease inhibitor, CST3, was reported to reduce the formation of osteoclasts by interfering with the late differentiation of osteoclast precursors . Studies have shown that inhibition of the NF‐κB pathway could relieve OP .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations